2014
DOI: 10.1016/j.ejphar.2014.09.034
|View full text |Cite
|
Sign up to set email alerts
|

NMDA receptor mediates chronic visceral pain induced by neonatal noxious somatic stimulation

Abstract: NMDA receptors (NMDAR) are important in the development and maintenance of central sensitization. Our objective was to investigate the role of spinal neurons and NMDAR in the maintenance of chronic visceral pain. Neonatal rats were injected with acidic saline adjusted to pH4.0 in the gastrocnemius muscle every other day for 12 days. In adult rats, NR1 and NR2B subunits were examined in the lumbo-sacral (LS) spinal cord. A baseline, visceromotor response (VMR) to graded colorectal distension (CRD) was recorded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 52 publications
(63 reference statements)
0
9
0
Order By: Relevance
“…The American Veterinary Medical Association (AVMA) has stated that “animal pain and suffering are clinically important conditions that adversely affect an animal's quality of life” (American Veterinary Medical Association, ). In addition to the negative impact that occurs at the time of the painful insult, untreated pain in both human and animal neonates may cause hypersensitivity to subsequent painful procedures (McCracken, Waran, Mitchinson, & Johnson, ; Page, ; Taddio, Goldbach, Ipp, Stevens, & Koren, ; Taddio, Katz, Ilersich, & Koren, ) and an increased propensity for long‐term pain (Hermann, Hohmeister, Demirakca, Zohsel, & Flor, ; Miranda et al., ; Page, ; Ren et al., ; Sanada et al., ; Walker, Tochiki, & Fitzgerald, ). These nociceptive responses can be alleviated with the appropriate use of analgesia during the initial painful stimulus (Page, ; Taddio et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The American Veterinary Medical Association (AVMA) has stated that “animal pain and suffering are clinically important conditions that adversely affect an animal's quality of life” (American Veterinary Medical Association, ). In addition to the negative impact that occurs at the time of the painful insult, untreated pain in both human and animal neonates may cause hypersensitivity to subsequent painful procedures (McCracken, Waran, Mitchinson, & Johnson, ; Page, ; Taddio, Goldbach, Ipp, Stevens, & Koren, ; Taddio, Katz, Ilersich, & Koren, ) and an increased propensity for long‐term pain (Hermann, Hohmeister, Demirakca, Zohsel, & Flor, ; Miranda et al., ; Page, ; Ren et al., ; Sanada et al., ; Walker, Tochiki, & Fitzgerald, ). These nociceptive responses can be alleviated with the appropriate use of analgesia during the initial painful stimulus (Page, ; Taddio et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the extensive literature of somatic pain, studies addressing the mechanism of visceral pain currently remain preliminary. Furthermore, the clinical therapeutic management of visceral pain remains less satisfactory than that of somatic pain, and studies investigating the mechanism of visceral pain with the aim of identifying new therapeutic targets have produced little success [ 1 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Animal studies have demonstrated that early life stress can lead to behavioral abnormalities and visceral hypersensitivity in adulthood. [3][4][5] Due to a high degree of central neuroplasticity in early life, either chronic or acute exposure to nociceptive stimulus during this period can lead to central sensitization-mediating visceral hypersensitivity. 6 Synaptic plasticity, mediated by the N-methyl-D-aspartate receptor (NMDAR), has been found to be involved in cerebral functions ranging from memory formation to the development of visceral hypersensitivity.…”
Section: Introductionmentioning
confidence: 99%